IMPLEMENTASI METODE ADDITIVE RATIO ASSESSMENT (ARAS) UNTUK MENENTUKAN PENERIMA BEASISWA DI MADRASAH IBTIDAIYAH HAYATUL ISLAMIYAH BERBASIS WEBSITE - Farhan Kamil; Fajar Agung Nugroho (Journal of Research and Publication Innovation, 2025)
Madrasah Ibtidaiyah Hayatul Islamiyah, located in Meruyung Village, Limo District, Depok City, is one of the schools targeted for scholarship recipients. Until now, the process of determining scholarship candidates begins with students submitting scholarship applications to the school principal. Subsequently, these applications are deliberated collectively by the school administration. However, disputes often arise during these deliberations due to the lack of definitive standards in the scholarship recipient selection process. Therefore, a Decision Support System application is needed to assist in decision-making using the Additive Ratio Assessment (ARAS) method. The assessment criteria used in this application include parents' income, number of dependents, distance from home to school, academic grades, and non-academic achievements. The ranking results show that the student most eligible to receive the scholarship is Arlan Aditya Rendra, with a total K Value of 0.927541. With this application, the process of determining scholarship recipients at Madrasah Ibtidaiyah Hayatul Islamiyah becomes easier, faster, and more accurate.